2002
DOI: 10.1128/jvi.76.15.7874-7882.2002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Cyclin-Dependent Kinase Inhibitors Inhibit Replication of Wild-Type and Drug-Resistant Strains of Herpes Simplex Virus and Human Immunodeficiency Virus Type 1 by Targeting Cellular, Not Viral, Proteins

Abstract: Pharmacological cyclin-dependent kinase (cdk) inhibitors (PCIs) block replication of several viruses, including herpes simplex virus type 1 (HSV-1) and human immunodeficiency virus type 1 (HIV-1). Yet, these antiviral effects could result from inhibition of either cellular cdks or viral enzymes. For example, in addition to cellular cdks, PCIs could inhibit any of the herpesvirus-encoded kinases, DNA replication proteins, or proteins involved in nucleotide metabolism. To address this issue, we asked whether pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(147 citation statements)
references
References 70 publications
10
135
1
1
Order By: Relevance
“…The antiviral xanthate D609 prevented HSV-1 replication by inhibiting the viral US3 protein kinase, protein kinase C, and viral protein phosphorylation (Walro and Rosenthal, 1997). Conversely, pharmacological cyclin-dependent kinase inhibitors exert their antiviral effects on herpes viruses by blocking cellular rather than viral proteins (Schang et al, 2002). Clearly the phosphorylation of both viral and cellular proteins is important for virus replication and protein kinase inhibitors exert their anti-viral effects by preventing phosphorylation of cellular and/or viral proteins.…”
Section: ) Discussionmentioning
confidence: 99%
“…The antiviral xanthate D609 prevented HSV-1 replication by inhibiting the viral US3 protein kinase, protein kinase C, and viral protein phosphorylation (Walro and Rosenthal, 1997). Conversely, pharmacological cyclin-dependent kinase inhibitors exert their antiviral effects on herpes viruses by blocking cellular rather than viral proteins (Schang et al, 2002). Clearly the phosphorylation of both viral and cellular proteins is important for virus replication and protein kinase inhibitors exert their anti-viral effects by preventing phosphorylation of cellular and/or viral proteins.…”
Section: ) Discussionmentioning
confidence: 99%
“…In addition to CDKs, p42/p44 MAPKs were found to interact with the purvalanol matrix, in most models: lugworm oocytes, Xenopus oocytes, porcine and human brains (Knockaert et al, 2000; data not shown), rat tissues (Knockaert et al, 2000; data not shown), rat hepatocyte primary cultures (data not shown) and in seven different mammalian cell lines (Figure 5b; Knockaert et al, 2000;Schang et al, 2002). These observations are quite striking, given the large difference between the IC 50 values of purvalanol for CDKs and MAPKs in vitro (Figure 4).…”
Section: Purvalanol Inhibits Mapks In Vivomentioning
confidence: 99%
“…After written informed consent was obtained, peripheral blood (PB) samples were obtained from patients enrolled in the Phase I dose-escalation study, as an ancillary study to better characterize the toxicity observed in the clinical study. 13 Patients bearing advanced/metastatic solid tumors were treated with repeated cycles of PHA-793887 administered as a 1 hour IV infusion on day 1, 8, 15 of a 4-week cycle, i.e., with treatment on days 1, 8, 15 followed by a 2 week resting period (day [16][17][18][19][20][21][22][23][24][25][26][27][28]. In 3 patients, before and after each injection, heparinized blood was taken on days 0, 2, 14 and 16 ( Fig.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…These observations could appear paradoxical in as much as recent studies have shown that replication of Herpes Simplex Virus (and other large DNA viruses) requires cellular proteins including CDKs. [14][15][16][17][18][19][20][21] One of the potential mechanisms accounting for these adverse effects might be the negative regulation of TLR signaling pathways by CDKi and/or GSK3β inhibition, as suggested by previous in vitro studies.…”
Section: Abstract: Tlr Dendritic Cells Cancer Herpes Cdk Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation